Basic Yoga Movement Guide at Dewata Studio Based on Augmented Reality - Setiawan, Panji Rachmat; Syefriani, Syefriani; Aprillio Vadri, Zackie (UIR PRESS, 2022)
Yoga is a meditation activity where someone decides whole mind to control five senses and body as a whole. Yoga members at Dewata Studio do yoga that is done with breathing exercise, body exercise, and meditation. All these exercises have benefits increase body fitness and overcoming depression. But many yoga members are having trouble to understand basic yoga movement. There are so many reasons why yoga members having trouble to understand basic movement, on of the reason is because COVID-19 pandemy, they can’t go to the Dewata Studio, so they can’t understand and explore basic yoga movement. As we know, basic yoga movement is the most important basic if we want to learn about yoga. There are 15 basic yoga movements at Dewata Studio that all yoga members must mastered before moving on to the next stage. This research help yoga members to understand and explore basic yoga movement by using an android application based on augmented reality. The application using by each member of Dewata Studio yoga member and give an explanation each movement. Using this application must under supervision of yoga trainers at Dewata Studio. With this application it is hoped that all yoga members at Dewata Studio can understand and explore basic yoga movement.